PERAN COMMUNITY BASED TOURISM DALAM MENDUKUNG KAMPUNG JELEKONG SEBAGAI DESA WISATA SENI DAN BUDAYA - Eva Mardiyana; Dendi Gusnadi; Tito Pandu Raharjo (Jurnal Cakrawala Ilmiah, 2023)
This research was conducted to describe the role of community based tourism in supporting Jelekong village as an arts and cultural tourism village. Research using the method used is desk research, this study utilizes secondary data as a source of literature. The results of this study indicate the role of the community in supporting Jelekong Village as an Arts and Culture Tourism Village. The results showed that positive community attitudes and participation in supporting cultural tourism villages seen from the many types of cultural activist groups as well as cultural actors in the Village Arts & Culture Tourism Village can encourage coordination and cooperation in tourism village organizations. Improved community skills and village policies also support the development of tourist villages. Tourism activities in this village can have multiple impacts on the growth of the community's life sector, especially economic improvement through additional income from tourist visits. The main motivation for the community in carrying out art activities is to maintain and enhance the uniqueness as an art and cultural tourism village in supporting sustainable tourism.